The effect of specific and non-specific opioids receptors antagonists on Exercise-Induced Hypoalgesia (EIH) - Cunha, Carolina Ortigosa (2015)
The opioid system is involved in a well-documented biological phenomenon named Exercise-induced Hypoalgesia (EIH) but the exact mechanism(s) are not clear. Studies demonstrate that exercise effects could be reversed by naloxone but there are no studies that evaluate the role of specific opioid receptors in the EIH levels. The present study aimed to evaluate the role of a non-specific (naltrexone) and specific opioids receptors (mu, kappa and delta) antagonists on the EIH levels induced by aerobic exercise in the Rota-Rod in a hundred and eighty (n=180) healthy male adult Sprague-Dawley rats. Rats were divided into five groups (naltrexone, vehicle, mu, kappa, delta) and each group was subdivided into high (67% EIH 100%), medium (34% EIH 66%) or low (EIH 33%) EIH profile level. After 3 days of habituation, EIH baseline measurements (percentage of response to 30 mechanical stimuli with 60g Von Frey monofilaments) at 1, 5, 10 and 20 minutes following exercise were assessed. In the day after the baseline measurements, thirty rats from each group (10 high, 10 medium and 10 low EIH) rats were injected with naltrexone hydrochloride, CTAP (mu receptor antagonist), GNTI (kappa receptor antagonist), Naltrindole hydrochloride (delta receptor antagonist), or vehicle (distilled water solution). Then, after 10 minutes (for naltrexone and vehicle), 20 minutes (for mu), 15 minutes (for kappa) and 10 minutes (for delta), EIH measurements were obtained again, just once. Data were analyzed with repeatedmeasurements ANOVA, followed by post-hoc Fisher test. Alpha was set at 0.05. Injection with the vehicle (distilled water) did not reduce the EIH (p=0.904), differently, naltrexone hydrochloride (p=0.000), kappa (p=0.002) and delta (p=0.000) antagonists drugs significantly reduced the EIH 1 minute following exercise when compared to baseline. It was concluded that rats with high EIH profile had a significant EIH reduction after injection of a non-specific and some specific opioid receptors antagonist (delta and kappa). The EIH effect, however, was just partially reduced, suggesting that others mechanism are involved in EIH phenomenon. The findings reveal that exercise induces hypoalgesia in healthy rats. More studies are needed to evaluate the phenomenon and the mechanisms of EIH in humans with painful disorders such as chronic musculoskeletal pain and orofacial pain